Multi-cellular human bronchial models exposed to diesel exhaust particles: assessment of inflammation, oxidative stress and macrophage polarization - Jie Ji; Swapna Upadhyay; Xiaomiao Xiong; Maria Malmlöf; Thomas Sandström; Per Gerde; Lena Palmberg (Particle and Fibre Toxicology, 2018)
Abstract Background Diesel exhaust particles (DEP) are a major component of outdoor air pollution. DEP mediated pulmonary effects are plausibly linked to inflammatory and oxidative stress response in which macrophages (MQ), epithelial cells and their cell-cell interaction plays a crucial role. Therefore, in this study we aimed at studying the cellular crosstalk between airway epithelial cells with MQ and MQ polarization following exposure to aerosolized DEP by assessing inflammation, oxidative stress, and MQ polarization response markers. Method Lung mucosa models including primary bronchial epithelial cells (PBEC) cultured at air-liquid interface (ALI) were co-cultured without (PBEC-ALI) and with MQ (PBEC-ALI/MQ). Cells were exposed to 12.7 μg/cm2 aerosolized DEP using XposeALI ®. Control (sham) models were exposed to clean air. Cell viability was assessed. CXCL8 and IL-6 were measured in the basal medium by ELISA. The mRNA expression of inflammatory markers (CXCL8, IL6, TNFα), oxidative stress (NFKB, HMOX1, GPx) and MQ polarization markers (IL10, IL4, IL13, MRC1, MRC2 RETNLA, IL12 andIL23) were measured by qRT-PCR. The surface/mRNA expression of TLR2/TLR4 was detected by FACS and qRT-PCR. Results In PBEC-ALI exposure to DEP significantly increased the secretion of CXCL8, mRNA expression of inflammatory markers (CXCL8, TNFα) and oxidative stress markers (NFKB, HMOX1, GPx). However, mRNA expressions of these markers (CXCL8, IL6, NFKB, and HMOX1) were reduced in PBEC-ALI/MQ models after DEP exposure. TLR2 and TLR4 mRNA expression increased after DEP exposure in PBEC-ALI. The surface expression of TLR2 and TLR4 on PBEC was significantly reduced in sham-exposed PBEC-ALI/MQ compared to PBEC-ALI. After DEP exposure surface expression of TLR2 was increased on PBEC of PBEC-ALI/MQ, while TLR4 was decreased in both models. DEP exposure resulted in similar expression pattern of TLR2/TLR4 on MQ as in PBEC. In PBEC-ALI/MQ, DEP exposure increased the mRNA expression of anti-inflammatory M2 macrophage markers (IL10, IL4, IL13, MRC1, MRC2). Conclusion The cellular interaction of PBEC with MQ in response to DEP plays a pivotal role for MQ phenotypic alteration towards M2-subtypes, thereby promoting an efficient resolution of the inflammation. Furthermore, this study highlighted the fact that cell–cell interaction using multicellular ALI-models combined with an in vivo-like inhalation exposure system is critical in better mimicking the airway physiology compared with traditional cell culture systems.